From the Factory of the World to Great Power: the chinese Mystery (Research, Society and Development, 2020)
This study is part of the panorama of concerns abaut the dynamics of chinese development. The guiding objective was to identify and analyze the relevant poinsts of the unfolding of chinese dynamism towards its hegemonic position in the internacional scenario. Studies on the subject demonstrate the preponderant role of the State in coordinating action of the vectors responsible for the country’s success worldwide. Investments in infrastructures of remarkable scope, organization of production zones, education with incentive to scientific-technological production and the construction of the vanguarda of the new retail using articial intelligence are outstanding elements of the chinese miracle. By way of conclusion, it reveals the omnipotente characteristics of the State in carrying out the reforms responsible for the insertion of China in the international scenario.